2011
DOI: 10.1016/j.vetmic.2011.02.028
|View full text |Cite
|
Sign up to set email alerts
|

The comparative performance of the single intradermal comparative tuberculin test in Irish cattle, using tuberculin PPD combinations from different manufacturers

Abstract: 13Ireland currently obtains its avian and bovine tuberculin purified protein derivatives (PPDs) from a 14 single source. Because problems of supply or quality cannot be discounted, it is prudent that Ireland

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 11 publications
2
18
0
Order By: Relevance
“…Although this is until now only stated for the skin test and in context of false negative test results [69]. The specificity of the Bovigam® assay tests varies also with the concentration and potency of PPDs [70], which can differ remarkably [71, 72]. These influences might explain to some extend the estimated low specificities of the Bovigam® assay.…”
Section: Discussionmentioning
confidence: 99%
“…Although this is until now only stated for the skin test and in context of false negative test results [69]. The specificity of the Bovigam® assay tests varies also with the concentration and potency of PPDs [70], which can differ remarkably [71, 72]. These influences might explain to some extend the estimated low specificities of the Bovigam® assay.…”
Section: Discussionmentioning
confidence: 99%
“…Variations in PPD production methods may lead to different antigenic profiles and therefore to qualitative differences between PPDs (Seibert and DuFour, 1940; Landi and McClure, 1969; Haagsma et al., 1982; Tameni et al., 1998). Moreover, the in vivo potency tests are inherently variable and of questionable precision, demonstrated by studies with repeated batch testing (Good et al., 2008). Importantly, a recent comparison of commercially available tuberculins has shown that if applied in a dose of 1 mg/ml, the majority of these tuberculins would not meet the required minimum dose of 2000 International Units (Bakker et al., 2009).…”
Section: Current Testing Strategiesmentioning
confidence: 99%
“…The other method is through slaughter surveillance that is entirely based on meat inspection at the slaughterhouse. The SCT has practical drawbacks such as subjectivity in result interpretation (the interpretation is based on observation and the recorded increases in skin‐fold thickness) and lack of specificity (false‐positive reactions caused by sensitization by other mycobacteria and by local inflammation) (Rua‐Domenech et al., ; Good et al., ; Fernández et al., ; Humblet et al., ; Bezos et al., ). The single comparative cervical tuberculin test (SCIT) is not used by the GOVs due to the lack of financial support.…”
Section: Introductionmentioning
confidence: 99%